Nivolumab in real-life clinical practice - M. A. Lyadova; O. A. Pardabekova; R. R. Shakirov; V. K. Lyadov; M. Yu. Fedyanin (Исследования и практика в медицине)
Purpose of the study. To evaluate the efficacy and tolerability of nivolumab in oncologic patients in real-life clinical seffings.Patients and methods. Analysis included 114 patients aged 26-96 years with melanoma (n = 64), non-small cell lung carcinoma (NSCLC) (n = 37) and metastatic colorectal cancer with high levels of microsatellite instability (MSI-H mCRC) (n = 13), receiving immune checkpoint therapy with nivolumab (3 mg/kg every 14 days). All patients underwent comprehensive examination including CT/chest radiography, CT/MRI/ultrasound of abdominal organs or PET-CT of the whole body and other investigations if necessary. Efficacy of treatment was assessed after every 6 courses on treatment or in case of signs of clinical progression. Treatment response was assessed using iRECIST 1.1 criteria.Results. Among patients with metastatic melanoma positive for BRAF gene mutation, receiving immune therapy objective treatment response was registered in 13.6%, tumor control — in 27.2%. In the group of patients, negative for BRAF gene mutation objective response was achieved in 27.5%, tumor control — in 41.4% patients. None of mCRC patients in our group achieved objective response, stable disease was observed in 30.8% of patients, progression — in 38.5% and unconfirmed progression — in 7.7% of patients. In NSCLC group complete response was observed in 2.7%, partial response — in 2.7%, stabilization — in 27.1%, unconfirmed progression — in 5.4%, progression — in 29.7% of patients. Safety analysis revealed the following significant adverse reactions: thyroiditis (n = 3), pneumonitis of 3 grade (n = 1), hepatitis of 3 grade (n = 1) and arthritis of 2 grade (n = 1). In 4 patients adverse reactions required treatment delay and prescription of glucocorticoids.Conclusion. Nivolumab treatment in real-life clinical practice is associated with a lower prevalence of adverse events compared to the results of clinical trials.